From "Involution" to "Capitalization": The "New Agriculture" and the "New Peasant"-A Case Study of Tobacco Growers in a Chinese Township (从"过密化"到"资本化"："新农业"与"新农民"--以湖北省恩施市烟叶种植农户为例的讨论) - Jiao (焦长权), Changquan; Chen (陈莹骄), Yingjiao (Zhongguo xiang cun yan jiu., 2017)
With the acceleration of the urbanization process and the transformation of the population structure, China's small peasant economy is breaking away from involutionary growth. At the same time, capital investment in family farms is increasing, leading to the capitalization of family farms and the rise of "new agriculture." Based on a case study of tobacco growers in a Chinese township, this article demonstrates how capital investment contributes to specialization and scale production in tobacco production and how a capitalized family farm operates, depending mainly on family labor and partly on rented land. As a typical new agriculture, tobacco production achieves the dual intensification of both capital and labor and manages to get out from the involution trap. This article argues that the capitalized family farm is not only a new type of economic subject but that it also shapes a new type of social subject. As the "new peasant," the holder of a capitalized family farm is a member of a social elite in villages and serves as the crucial social force in the transformation of village society. 伴随城市化的快速发展和农村人口结构的转型，中国的小农经济正逐渐摆脱"过密化"陷阱。同时，农业生产中的资本投入日益增长，家庭农场日益"资本化"，"新农业"获得了空前的发展。文章以中国恩施地区烟叶生产为例，阐述了资本投入对烟叶专业化、规模化生产的关键作用，分析了资本化家庭农场的经营方式：其主要依赖家庭劳动力（少部分季节性雇佣劳动力），并通过土地流转实现适度规模经营。烟叶生产是一种典型的"新农业"，它在家庭农场中实现了资本和劳动的"双密集"，摆脱了"过密化"陷阱。作者认为，资本化的家庭农场不仅形成了一种"新农业"（新型经济主体），更塑造了一群"新农民"（新型社会主体），他们是村庄中的精英群体，对村庄社会转型具有重要意义。 (This article is in English.)